PENGARUH PEMBERDAYAAN KARYAWAN DAN KEPUASAN KERJA TERHADAP KOMITMEN ORGANISASIONAL PADA PT. RADITYA DEWATA PERKASA - Radnyanamastri, Ni Putu Adrika; Ardana, I Komang (E-Jurnal Manajemen; Vol 6 No 11 (2017), 2017)
Organizational commitment is part of a tool in human resource management. The results obtained by the company in realizing its objectives are determined by the commitment of an employee to the company. The purpose of this study is to determine the effect of employee empowerment and job satisfaction on organizational commitment. This research was conducted at PT. Raditya Dewata Perkasa. The number of samples taken as many as 88 employees, with the method of saturated samples. Data were collected through interviews and questionnaires. Analytical techniques used are multiple linear regression, confirmatory analysis techniques and classical assumption test. Based on the results of the analysis found that employee empowerment and job satisfaction have a positive effect on organizational commitment. This shows that the increasing employee empowerment and job satisfaction hence increasing organizational commitment of employees at PT. Raditya Dewata Perkasa. Keywords: Employee Empowerment, Job Satisfaction, Organizational Commitment